Pancreatic β-cell defects in women at risk of type 2 diabetes - Pimenta, W. P. [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Aragon, F. F. [UNESP]; Padovani, Carlos Roberto [UNESP] (Elsevier, 2004)
We evaluated insulin release and insulin sensitivity in women with basal and/or postprandial hyperglycemia but normal oral glucose tolerance test (OGTT) in previous pregnancy (GHG). These women were individually matched with females without previous hyperglycemia (NGT). Both groups consisted of normal glucose-tolerant women at the time of this study. They underwent OGTT (75g; n= 32 pairs) and hyperglycemic clamp experiments (10mmoll-1; n=27 pairs) with plasma glucose, insulin, and C-peptide measurements and calculation of insulinogenic index, first- and second-phase insulin release, and insulin sensitivity index (ISI). The GHG group showed higher glycosylated hemoglobin levels (6.2±0.6% versus 5.8±0.8%; P<0.05); lower insulinogenic index at 30min (134.03±62.69pmolmmol-1 versus 181.59±70.26pmolmmoll-1; P<0.05) and diminished C-peptide response in relation to glucose (4.05±0.36nmolmmol-1 versus 4.23±0.36nmolmmol-1; P<0.05) at OGTT. Both groups did not show difference in insulin secretion and ISI by hyperglycemic clamp technique. We concluded that in up to 12 years from index pregnancy, women with previous GHG, presenting normal glucose tolerance and well-matched with their controls, showed β-cell dysfunction without change in ISI. As women with previous GHG are at risk of type 2 diabetes, β-cell dysfunction may be its primary defect. © 2003 Elsevier B.V. All rights reserved.
Keywords: Gestational hyperglycemia; Insulin release; Insulin sensitivity; Type 2 diabetes; C peptide; glucose; glycosylated hemoglobin; adult; calculation; clinical article; controlled study; female; glucose blood level; high risk population; human; hyperglycemia; insulin blood level; insulin release; insulin sensitivity; non insulin dependent diabetes mellitus; oral glucose tolerance test; pancreas disease; pancreas islet beta cell; postprandial state; pregnancy; pregnancy diabetes mellitus; protein blood level; risk assessment; Blood Glucose; C-Peptide; Diabetes Mellitus, Type 2; Female; Food; Glucose Clamp Technique; Glucose Tolerance Test; Hemoglobin A, Glycosylated; Humans; Hyperglycemia; Insulin; Insulin Resistance; Islets of Langerhans; Pregnancy; Risk Factors